Short Term Clinical Outcomes in Spine Surgeries. A Descriptive Cross Sectional Study in a Tertiary Care Hospital - Muhammad Idris Khan, Adnan Munir, Syed Aziz, Hubab Ali, Syed Mansoor Shah, Fawad Nasir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out the short-term post operative outcomes faced by patients undergoing various spine procedures. Study Setting: Neurosurgery department Khyber Teaching Hospital Peshawar Khyber Pakhtunkhwa. Study Duration: January 2022 to January 2023 Study Design: Cross-sectional study (descriptive). Material and Methods: After taking approval from the hospitals ethical and research committee a single center review of the medical records of all patients who underwent common surgical procedures of the spine were collected and patients followed for short term post -operative outcomes. Data was analyzed by using the statistical software SPSS version 23.0 and the results were presented in the form of tables and charts. Results: Out of 360 patients included in the study, 206 (57.2%) were males and 154 (42.8%) were females with a mean age of 41.3 ± 13.4. The highest percentage of patients presented with a PIVD at L4-L5 (n=176, 48.9%). It turns out that aged patients had more VRS scores compared to young candidates after surgery (p-value= 0.05) and patients who underwent only decompressive laminectomies had noticeable reduction frequency of discitis (p-value= 0.40) and a remarkable improvement in the VRS score after surgery (p value=<0.01) as compared to other procedures. Conclusion: Even though laminectomy, being the procedure of choice in so many cases, significantly treats neurogenic claudication, still unresolved back pain is the most common complaint made by patients in the post operative period. However, despite complications, patient satisfaction rates have improved over the period of time. Keywords: Post-operative complications, laminectomy, discectomy, neurosurgery.